2020
DOI: 10.1007/s11357-020-00205-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social distance measures on COVID-19 epidemics in Europe: an interrupted time series analysis

Abstract: Following the introduction of unprecedented "stay-at-home" national policies, the COVID-19 pandemic recently started declining in Europe. Our research aims were to characterize the changepoint in the flow of the COVID-19 epidemic in each European country and to evaluate the association of the level of social distancing with the observed decline in the national epidemics. Interrupted time series analyses were conducted in 28 European countries. Social distance index was calculated based on Google Community Mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 10 publications
4
86
0
2
Order By: Relevance
“…(Röst et al 2020) It has been shown with the use of mobility and COVID-19 epidemiology data from the European countries that successful restrictive policy can significantly contribute to the suppression of the SARS-CoV-2 pandemic. (Vokó and Pitter 2020) Furthermore, consistently with the low level of seropositivity reported in our study, the rate of incident cases registered by the National Public Health Center in Hungary throughout the timeframe of the testing was low as well. However, besides the early containment efforts, there have been a few additional potential protective factors suggested against COVID-19, such as BCG vaccination or blood type 0 which is representative in the Hungarian population.…”
Section: Discussionsupporting
confidence: 87%
“…(Röst et al 2020) It has been shown with the use of mobility and COVID-19 epidemiology data from the European countries that successful restrictive policy can significantly contribute to the suppression of the SARS-CoV-2 pandemic. (Vokó and Pitter 2020) Furthermore, consistently with the low level of seropositivity reported in our study, the rate of incident cases registered by the National Public Health Center in Hungary throughout the timeframe of the testing was low as well. However, besides the early containment efforts, there have been a few additional potential protective factors suggested against COVID-19, such as BCG vaccination or blood type 0 which is representative in the Hungarian population.…”
Section: Discussionsupporting
confidence: 87%
“…This was demonstrated in 28 European countries, where the most probable point of change in the course of the COVID-19 epidemic showed a dose-response association of the observed flattening of the epidemic curve with an increasing social distancing index (SDI). Countries in the highest SDI quartile achieved a statistically significant decline in the incidence and prevalence of the epidemic [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the low number of included patients limited the statistical power of this study. Fortunately, the number of known COVID-19 cases remained relatively low in Hungary, probably owing to the timely introduction of social distancing interventions [32]. Indeed, only 60 new patients were diagnosed with SARS-CoV-2 infection after our database was finalized at our institution until the end of May (Tamás Berényi, personal communication).…”
Section: Discussionmentioning
confidence: 99%